GROWTH RESPONSE AND PRODUCTION EFFICIENCY OF BROILER CHICKS TREATED BY DIFFERENT ZEOLITE SPREADING FREQUENCY ON LITTER BASE - Freddy Pattiselanno; Sangle Y. Randa (Jurnal Zeolit Indonesia, 2006)
The objective of this research was to study the growth and efficiency of broiler productivity. The research was conducted through the application of zeolite spreading treatment into the broiler housing in Non-ruminant Research Station of Animal Science Laboratory of Papua State University. Study was arranged by Randomized Sample Design with four treatments: P0 (control; without zeolite spreading); P1 (once time spreading during the research period); P3 (three times application of spreading during the research period); and P5 (five times of spreading or once a week during the research period). The application of zeolite spreading was not significantly influenced the rate growth of broiler, though there is a tendency increasing weight gain along with the increased in zeolite spreading level on the litter base. P3 (three times of zeolite spreading during research) produce the feed efficiency of 0.53. Economically, Income Over Feed Chick and Zeolite Cost (IOFCZC) per head per housing unit with the application of zeolite spreading more demand compared to housing units without spreading treatment.